The hobbit. The desolation of Smaug - Jackson, Peter, 1961-; Walsh, Fran, 1959-; Boyens, Philippa; McKellen, Ian; Blanchett, Cate, 1969-; Nesbitt, James, 1965-; Bloom, Orlando, 1977-; Lilly, Evangeline, 1979-; Stott, Ken, 1955-; Warner Home Video (Firm) (Burbank, CA : Distributed by Warner Bros. Entertainment Inc., 2014)
Bilbo Baggins continues on in his journey with the wizard Gandalf and thirteen dwarves, led by Thorin Oakenshield, on an epic quest to reclaim their lost Dwarf Kingdom of Erebor.
Originally released as a motion picture in 2013.
Based on the novel by J.R.R. Tolkien.
Title from container.
For special features see interactive menu on the disc.
Some copies may not contain special features. Contact your local library for further information or to obtain a copy with special features.
Ian McKellen, Cate Blanchett, James Nesbitt, Orlando Bloom, Evangeline Lilly, Ken Stott, Martin Freeman, Stephen Fry, Lee Pace, Benedict Cumberbatch, Sylvester McCoy, Richard Armitage, Aidan Turner, Luke Evans, Graham McTavish, William Kircher.
Keywords: Middle Earth (Imaginary place) -- Drama; Baggins, Bilbo (Fictitious character) -- Drama; Hobbits (Fictitious characters) -- Drama; Fantasy films; Feature films; Science fiction films